Factors affecting community pharmacists' intention to provide smoking cessation services in Manila City using the theory of planned behavior - Escote, Jemimah Gyra C.​; Ordoñez, Trissia Marie B.​; Sombillo, Maria Celine Isabel V.​
Implementation of smoking cessation services is important due to the significant effects of cigarette use to morbidity and mortality rates. Provision of the said services by community pharmacists are proven to be effective. However, there is a lack of these services in the Philippines despite the presence of international and local support and guidelines. Hence, this study aimed to determine the factors that might affect the intention of community pharmacists to provide smoking cessation services in Manila City using the Theory pf Planned Behavior (TPB). This study used cross-sectional correlation design which utilized self-administered questionnaire. Descriptive statistics and multiple linear regression were used in data analysis.